Etika Sufistik dalam Pencegahan Bullying: Perspektif Tafsir Isyari Ibnu ‘Ajibah - Muhammad Husein; Norhidayat; Ahmad Mujahid (Jurnal Riset Multidisiplin Edukasi, 2026)
This research seeks to revitalize Sufi ethics as a transformative behavioral framework to prevent bullying in the modern era, focusing on the interpretation of QS. Al-Hujurat [49]: 11 through the perspective of Ibn ‘Ajibah. The study employs a Sufi hermeneutic approach consisting of three methodological steps: textual explanation, uncovering esoteric meanings (ishari), and applying these insights to contemporary ethical and spiritual contexts. The findings indicate that bullying is not merely a social phenomenon but a manifestation of spiritual maladies such as arrogance, malice, and hypocrisy. Textual analysis of the verse reveals a hierarchical prohibition, ranging from outward social conduct to deeper spiritual transgressions. Sufi exegesis highlights fundamental concepts—such as spiritual unity, divine manifestation (tajalli), and self-purification (tazkiyat al-nafs)—as the moral foundation for countering bullying. When applied to cyberbullying, these values yield digital ethical principles, including benevolence in digital interactions, online humility, and digital communal harmony. The research concludes that the revitalization of Sufi ethics offers a more holistic and profound solution compared to conventional approaches by emphasizing the transformation of self-consciousness as the primary preventive measure. These results suggest practical implementations in character education that integrate digital and spiritual dimensions, restorative counseling based on Sufi values, and the integration of spiritual approaches with psychological interventions in bullying cases